Kejadian Stunting pada Balita Berhubungan dengan Pemberian ASI eksklusif Selama 1000 Hari Pertama Kelahiran - Harismayanti, Harismayanti; Mansur, Rona Febriyona (Health Information : Jurnal Penelitian, 2023)
The phenomenon of exclusive breastfeeding coverage that is still low in the long term will have implications for children's growth and development. This study explores the relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the Working Area of the Limboto Health Center, Gorontalo Regency. By involving 93 respondents of mothers of toddlers aged 7-24 months, this study used a cross-sectional, quantitative approach for exclusive and qualitative breastfeeding history variables with in-depth interviews of exclusive breastfeeding factors, data analysis using the Chi-square test method. Most toddlers in the very short (16.1%), and short (14.0%) categories, then those who do not receive exclusive breastfeeding tend to be stunted (p = 0.001). Factors of exclusive breastfeeding include health facilities that are far enough away so that health services and counseling obtained are not optimal, lack of maternal understanding of the importance of nutritional status during the first 1000 days of life or during pregnancy until the child is 2 years old, mothers with a history of SEZ conditions, history of anemia and irregular consumption of Fe tablets during pregnancy mostly give birth to children with stunting. Efforts to overcome the problem of stunting require good cross-sectoral cooperation. Further research is needed by paying attention to cultural and contextual factors.